Challenges of Indonesian Industrialization and Trade Problems in the Industrial Era 4.0 for the Indonesian Economy and Government Policy Breakthrough - Yuli Noor Kusumawati; Seto Indarto (Eduvest - Journal of Universal Studies, 2024)
Industry 4.0 was born in 2011, for Indonesia it has brought benefits to industrialization and trade starting from 24-hour production automation, time efficiency because the process is fast and connected to the internet for unlimited distances with the help of internet signals, saving minds because AI-based technology is able to think to answer our questions and the ability to store and provide big data, production and trading costs are clearly more efficient because paperless, sending data without couriers, calculating the use of production inputs is more accurate so it is more economical. However, besides the advantages, there are also many challenging problems in Indonesia, starting from misuse of online media platforms, cyber crime (illegal taking of company data/hacking, misuse of other people's personal data for online fraud and illegal investment) which causes state losses of more than Rp. 232, 646 trillion until 2023. Therefore, the government has issued a policy breakthrough in the form of policies that have a broad impact and legal regulations that provide strict limits and sanctions.